PEMBUATAN PEKTIN DARI LIMBAH KULIT JERUK (Citrus sinensis) DENGAN METODE EKSTRAKSI GELOMBANG ULTRASONIK MENGGUNAKAN PELARUT ASAM SULFAT (H2SO4) - Ayu Arimpi, Setiaty Pandia (Universitas Sumatera Utara, 2019)
Pectin can be utilized in various industries of making jelly, jam, gelling, thickener, stabilizer and emulsifier. In this study the extraction of pectin from orange peel (Citrus sinensis) using ultrasonic waves and sulfuric acid (H2SO4) was conducted to determine the effect of variation in settling time and concentration of the alcohol as the pectin filtrate precipitating material on the characteristics of the pectin produced. The study was carried out with 30 minutes extraction time, extraction temperature of 70 oC using H2SO4. Variations carried out were settling time for 14 hours, 16 hours, 18 hours and 20 hours, and concentration of the alcohol ; 65%, 75%, 85% and 95%. Characteristics of pectin produced with successive characteristics: yield ranged from 16.44%-22.44%; moisture content from 4.0-9.45%; ash content of 2.34%-5.54%; equivalent weight of 510.20-865.07 mg; methoxyl content of 7.35%-10.79%; and galacturonic content of 63.71%-95.74%. The 18-hour settling time with 95% ethanol produced the most yield with the best pectin characteristics that met IPPA (International Pectin Producers Association) standards.